Teologi Misi Dalam Injil Lukas: Penundaan Parousia Sebagai Lensa Tafsir? - Deky Hidnas Yan Nggadas (Vieka Wahana Semesta, 2023)
Abstract: This article is a critical interaction with the views of liberal theologians regarding the theology of non-Jewish missions in the Gospel of Luke. By using qualitative research methods, especially literature review, the researcher examines the views of every liberal theologian who has different views on the theology of mission in the Gospel of Luke. From the results of this study, we found an interesting parallel that Paul emphasized regarding the universal human condition under the dominion of sin in Romans 1:18-32. And of course, this was the image that both Wilson and Tsuchiya wanted to see but they failed to bring it up in their observations. The sinful nature described by Luke does not lead to any other conclusion except that the gentiles, like the Jews, need the Gospel of salvation. Abstrak: Artikel ini adalah sebuah interaksi kritis terhadap pandangan para teolog liberal mengenai teologi misi non Yahudi dalam Injil Lukas. Dengan menggunakan metode penelitian kualitatif, khususnya kajian pustaka, peneliti mengkaji setiap pandangan teolog liberal yang memiliki pandangan berbeda tentang teologi misi dalam injil Lukas. Dari hasil penelitian ini didapati paralel menarik yang ditekankan Paulus mengenai kondisi universal manusia di bawah kekuasaan dosa dalam Roma 1:18-32. Dan tentu saja, ini adalah gambaran yang ingin dilihat baik oleh Wilson maupun Tsuchiya namun mereka gagal memunculkannya dalam pengamatan mereka. Natur keberdosaan yang digambarkan Lukas tersebut memang tidak memimpin kepada kesimpulan lain lagi kecuali bahwa gentiles, sama seperti orang-orang Yahudi, membutuhkan Injil keselamatan.